Significance of fruit and vegetable allergens: Possibilities of its reduction through processing. Issue 2 (17th February 2018) - Vanga, Sai Kranthi; Jain, Mohit; Raghavan, Vijaya
ABSTRACT: Fruit and vegetable allergies are prevalent commonly in adults, infants, and children all around the world, but more importantly in Europe and North America. The only solution is complete abstinence from the responsible food, which can be very difficult due to their presence in the form of hidden or undeclared ingredients. Various studies have shown the direct effect of processing on the secondary structure of proteins that can mitigate the allergic properties. The impact of these processing techniques on fruit and vegetable allergies have shown limited success due to the fact that they have multiple allergens that are especially heat stable. Apples, kiwi, peach, and melons are common fruits, whereas celery and carrot are the common vegetables that can result in allergic reactions for some portion of the population upon exposure. Abbreviations: IgE: immunoglobulin E, OAS: oral allergy syndrome, nsLTP: nonspecific lipid transfer proteins, LTP: lipid transfer proteins, HPP: high-pressure processing, PEF: pulsed electric field, CD: circular dichroism, pI: isoelectric point, DBPCFCs: double-blind placebo-controlled food challenges